2017
DOI: 10.1097/bsd.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cytokines, Sensory Tests, and Self-reported Pain Levels After Manual Treatment of Low Back Pain

Abstract: Self-reported pain was reduced with MT and sham ultrasound treatment 24 hours after treatment, but inflammatory markers within venous circulation and quantitative sensory tests were unable to differentiate between study groups. Therefore, we were unable to characterize mechanisms underlying chronic LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 69 publications
0
38
1
Order By: Relevance
“…[39] Therefore, OMT could reduce the release of cytokines and the sympathetic activity creating a cascade of biological and neurological events able to modulate both inflammatory and ANS mechanisms. [40,41] …”
Section: Discussionmentioning
confidence: 99%
“…[39] Therefore, OMT could reduce the release of cytokines and the sympathetic activity creating a cascade of biological and neurological events able to modulate both inflammatory and ANS mechanisms. [40,41] …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, OMT seems to be associated with a reduction of pro-inflammatory substances both in vitro (Meltzer and Standley, 2007 ) and in vivo (Licciardone et al, 2012 , 2013 ) hypothesizing an anti-inflammatory role of OMT, although only partially confirmed by recent clinical-based research (Degenhardt et al, 2014 ).…”
Section: Clinical Applications and Implicationsmentioning
confidence: 98%
“…Based on the current evidence, it is difficult to identify what are the main neurobiological elements involved during and after administering an osteopathic session. Indeed, it has been suggested that possible OMT mechanisms are modulated by the autonomic nervous system (ANS) functions (Ruffini et al, 2015;D'alessandro et al, 2016), where interoceptive mechanisms might be involved (Cerritelli et al, 2020), leading to a reduction of pro-inflammatory cytokine release (Licciardone et al, 2012;Degenhardt et al, 2017). This evidence was shown both in vitro (Zein-Hammoud and Standley, 2015) and in vivo (Degenhardt et al, 2017), suggesting an anti-inflammatory role of OMT (D'alessandro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been suggested that possible OMT mechanisms are modulated by the autonomic nervous system (ANS) functions ( Ruffini et al, 2015 ; D’alessandro et al, 2016 ), where interoceptive mechanisms might be involved ( Cerritelli et al, 2020 ), leading to a reduction of pro-inflammatory cytokine release ( Licciardone et al, 2012 ; Degenhardt et al, 2017 ). This evidence was shown both in vitro ( Zein-Hammoud and Standley, 2015 ) and in vivo ( Degenhardt et al, 2017 ), suggesting an anti-inflammatory role of OMT ( D’alessandro et al, 2016 ). McGlone et al (2017) argued that OMT could putatively decrease cytokine production and sympathetic activity, generating a cascade of physiological and neurobiological events, which in turn can modulate the inflammation and the ANS reactivity.…”
Section: Introductionmentioning
confidence: 99%